p53: A double-edged sword in tumor ferroptosis - Haixia Ji; Wenzhe Wang; Xia Li; Xiaoying Han; Xinyu Zhang; Juan Wang; Changxiao Liu; Luqi Huang; Wenyuan Gao (Pharmacological Research, 2022)
Ferroptosis is a type of lipid peroxidation-induced cell death that can be regulated in various ways, from changing the activity of antioxidant enzymes to the levels of transcription factors. The p53 tumor suppressor gene is the ''guardian of the genome'' and is involved in controlling cell survival and division under various pressures. In addition to its effects on apoptosis, autophagy, and cell cycle, p53, through the way of transcription dependent or independent two-way, also regulates the biological processes of tumor cell sensitivity to ferroptosis, including the metabolism of amino acids, nicotinamide adenine dinucleotide phosphate, and lipid peroxidation, as well as the biosynthesis of glutathione, phospholipids, NADPH and coenzyme Q10. As reviewed here, we summarized the metabolic network of p53 and its signaling pathway in regulating ferroptosis and elucidated possible factors and potential clinical application of p53 regulating ferroptosis. This review will provide a basis for further understanding the role of p53 in tumor ferroptosis and new strategies for cancer therapeutic avenues.